POTENSI EKSPOR OLAHAN KAKAO INDONESIA DI PASAR INTERNASIONAL MELALUI ASPEK DAYA DUKUNG, ASPEK PEMASARAN DAN ASPEK KEBIJAKAN - Mawar Melania; Ernawati HD; Mirawati Yanita (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2020)
The purpose of this research is to know export potention of cocoa products Indonesian in the international market through supporting aspects, marketing aspects and policy aspects. The data needed are the export volume, value and price of cocoa products (cocoa paste, cocoa butter, cocoa powder and chocolate). Data obtained from the official website of 1) Food and Agriculture Organization, 2) United Nation Commodity Trade, 3) Trade Map-International Trade Statistic, 4) World Bank, 5) The Central Bureau of Statistics and 6) The Directorate General of Plantation. This research used descriptive analysis to examine export potention, RCA and ISP to analize the competitiveness of cocoa products and trend method to forecast analysis. The result showed that Indonesian have potention to export cocoa products through from some aspect : 1) resources aspect are increased area harvested of 8,56 percent and the production of cocoa beans is 5,6 percent per year; 2) marketing aspect, Indonesia have the main target market is United States America. This country is a developed countries with high population growth and GDP per capita, so that will impact on the consumers; 3) policy aspect, Indonesian has implemented a policy of export tax cocoa beans to encourage the cocoa industries.